ANALISIS BAGI HASIL TANGKAP IKAN PADA NELAYAN DI PULAU BAAI KOTA BENGKULU - Ryan Rakhmat Ardhyanto; Mardalena Mardalena; Imam Asngari (Universitas Bengkulu, 2020)
This research aims to determine the mudharabah profit sharing system for fishermen in the Kampung Melayu sub-district, Bengkulu City. The data used are primary data from 95 selected samples. The profit sharing system for the mudharabah muqayyah carried out by boat owners and fishermen is 4 (four) types, namely 50 percent share for boat owners 50 percent fishermen, 60 percent share for boat owners 40 percent share for fishermen, 30 percent share for boat owners 70 percent for fishermen, and labor fishermen who are paid a daily wage of Rp. 70.00 per day. The profit sharing system used is profit and loss sharing, none of which uses revenue sharing. The impact of the sharing system for 50 percent of boat owners and 50 percent of fishermen is more profitable for fishermen than other systems.